Communicative Change Management: The Strategic Power of Language in Driving Workplace Productivity - Elok Cahyaning Pratiwi; Anis Sirojuddin Suryo Negoro; Risa Amalia Murzrifah; Yusuf Rahman Al Hakim (RISK : Jurnal Riset Bisnis dan Ekonomi, 2026)
The high failure rate of organizational change initiatives, despite adequate strategies and technologies, indicates that language as a mechanism for constructing the meaning of change is still frequently overlooked in change management practice. This study aims to develop a language-based conceptual model of communicative change and explain how managerial language shapes sensemaking processes and influences workplace productivity during organizational change. The study uses a qualitative approach with a Constructivist Grounded Theory design within an interpretive-constructivist paradigm. The research context focuses on organizations undergoing or recently experiencing change, with leaders, managers, and affected employees selected through theoretical sampling. Data were collected through in-depth semi-structured interviews, participant observation, and analysis of organizational documents, and then analyzed iteratively using initial coding, focused coding, and theoretical coding with the constant comparative method. The findings produced a core category, namely language-mediated sensemaking in organizational change, with four major themes: framing language and perception of change, emotional resonance of managerial narratives, language-driven alignment and resistance, and discursive pathways to productivity. The process model shows a flow from language framing, meaning construction, and affective responses to action alignment and productivity. This study enriches language-based change management theory and offers practical guidance for leaders to design change communication that is clearer, more contextual, and sensitive to productivity.